Ação da Quinacrina, inibidor de PLA2, sobre a proteína beta-amiloide em modelo de Doença de Alzheimer em Drosophila melanogaster - Santos, Luiz Gabriel Alves (2020)
Alzheimer's disease is a progressive neurodegenerative disease that results in cognitive and motor deficit and it also has no cure. It is associated with the production pathway of the peptide amyloid-β (Aβ), derived from the amyloid precursor protein (APP) and the enzyme that cleaves this protein, producing Aβ, is the β-secretase (BACE) enzyme. Recent studies show the relationship between the production of Aβ and the accumulation of this molecule witch forms oligomers, with the presence of the phospholipase A2 enzyme (PLA2). Considering the limitation in the discovery of new drugs that regulate this disease, new alternatives have been studied, including quinacrine, which is a PLA2 inhibitor, and the relationship in the regulation of amyloid-β protein. Therefore, this study has been done in Drosophila melanogaster, which is a model that expresses the APP and BACE genes. The objective of this research has been to evaluate the action of quinacrine on amyloid-beta protein in Alzheimer's Disease model in Drosophila melanogaster. Preliminary results have been obtained in silico of Drosophila’s with the quinacrine molecule. Later, a pharmacokinetic prediction of this drug has been made, that allowed us to observe pharmacokinetic parameters in pre-established systems, such as intestinal absorption and permeability in the central nervous system. This analysis revealed that quinacrine has similarities with the drug most used today against Alzheimer, which is rivastigmine. We also observed that quinacrine was not able to cause toxicity in Drosophila model during survival treatment, at concentrations of 6.25 to 200 μg/mL, and promoted an increase in climbing in the locomotor assay, mainly at the lowest dose of 6.25 μg/mL, as well as reduced amyloid-β levels by biochemical assay in that same concentration, and altered the expression of nine metabolites in this same concentration in relation to the control group in the analysis of metabolic groups (metabolomics). It was found that quinacrine has a great potential to regulate and inhibit Aβ, through the inhibition of PLA2 in a mimetic model of Alzheimer's Disease in Drosophila melanogaster.